Racemization of Enantiopure Alcohols Using Two Mutants of Thermoanaerobacter pseudoethanolicus Secondary Alcohol Dehydrogenase. Issue 46 (6th December 2021) - Musa, Musa M.
Abstract: Racemization of enantiopure alcohols is the key step to accomplish a dynamic kinetic resolution, and thus overcome the intrinsic drawback of 50 % yield with high enantioselectivity that is associated with kinetic resolution. Herein, the concurrent use of I86A and W110G mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase ( Te SADH) in racemization of enantiopure phenyl‐ring‐containing alcohols is reported. The efficiency of this bienzymatic racemization approach is also compared with that reported previously using W110G Te SADH and is marginally more efficient. Abstract : The concurrent use of I86A and W110G mutants of Thermoanaerobacter pseudoethanolicus secondary alcohol dehydrogenase ( Te SADH) in racemization of enantiopure phenyl‐ring‐containing alcohols is reported.